DUKUNGAN KELUARGA SEBAGAI DETERMINAN KUNJUNGAN ANTENATAL CARE (ANC) - Patimah, Patimah; Zulliati, Zulliati; Lestari, Yayuk Puji; Suhartati, Susanti (Institut Teknologi dan Kesehatan Muhammadiyah Kalimantan Barat, 2026)
Background: The government has developed strategies and policies in the form of health improvement programs to reduce the Maternal Mortality Rate, including improving Antenatal Care. The family has a significant role in determining the health status of the mother. The support provided by the family creates a sense of peace and happiness within, so that pregnant women ultimately find it easier to adjust to their pregnancy. Objective: To find out the correlations between family support and ANC visits in the working area of Sungai Turak Health Center, Hulu Sungai Utara Regency. Methode: This type of research with correlational study design with cross sectional approach. Population of 80 pregnant women and sample of 45 respondents at Sungai Turak Health Center in April 2025, taken by purposive sampling technique. Data collection using questionnaires. Data were analyzed using Chi-Square test. Result: Family support is mostly supportive, namely 34 people (75,6%). ANC check-up visits are mostly complete, namely 40 people (88.9%). Conclusion: There was a correlations between family support and ANC visits in the working area of Sungai Turak Health Center, Hulu Sungai Utara Regency with a p value (0.010<0.05). Midwives are advised to motivate pregnant women to have regular ANC check-ups, blood pressure checks, improve the quality of ANC health services, and intensify counseling and information and education counseling for high-risk pregnancies.